A comparative study of large karst cave point cloud registration in various scanning modes. Issue 374 (2nd September 2020) - Guo, Yu; Xia, Yonghua; Yang, Xiangying; Yang, Minglong; Bai, Hongqiang; Feng, Ming
Abstract : With the development of 3D laser scanning technology, terrestrial 3D laser scanning technology has been applied in the field of underground space exploration. In this study, three different scanning modes were applied to collect data. Data collection was carried out in a branch hole of a karst cave in Yiliang County, Yunnan Province, China. After filtering, denoising and registration of the acquired cloud data. We analysed the registration effect and accuracy of the two adjacent stations under different scanning modes. Finally, the accuracy report of point cloud data obtained under different scanning modes was generated, and the application conditions of different scanning methods and the efficiency of scanning operation were discussed and analysed. The study would provide certain significant guidance for actual production.